Crystal structure characteristics, dielectric loss, and vibrational spectra of Zn-rich non-stoichiometric Ba[(Zn1/3Nb2/3)1−xZnx]O3 ceramics. (31st July 2017) - Li, Jianzhu; Xing, Chao; Qiao, Hengyang; Chen, Huiling; Yang, Jun; Dong, Helei; Shi, Feng
Abstract: Zn-Rich non-stoichiometric Ba(Zn1/3 Nb2/3 )1− x Zn x O3 (BZNZ) ( x = 0.01, 0.02, 0.03, 0.04) ceramics were prepared by the solid-state reaction method at 1500 °C for 2 h. The crystal structures and morphologies were analyzed by x-ray diffraction (XRD) and scanning electron microscopy. The vibration modes were obtained by Raman scattering spectroscopy and Fourier transform far-infrared (FTIR) reflectance spectroscopy. Rietveld refinement was performed for the XRD data. The relationship between crystal structures, dielectric properties, and phonon modes was analyzed in detail. XRD results show that the main phase is Ba(Zn1/3 Nb2/3 )O3 . The Raman results displayed that the ordering structure of BZNZ transformed from 1:2 to 1:1 when x changed from 0.02 to 0.04, and the dielectric losses have a positive correlation with the full width at half maximum values of the A 1g (O) and E g (O) modes. The FTIR spectra were analyzed by the Kramers–Krönig method to obtain the real parts ( ε ′) and the imaginary parts ( ε ″) of the dielectric constant. When x = 0.02, the sample possesses uniform grains with clear boundaries and the lowest dielectric loss value (tan δ = 5.5 × 10 ‒4 ) due to the largest packing fraction.